Rank and MIMO mode adaptation in LTE - Jonna, Thulasiram; Reddy, Siva Kishore; Milleth, J. Klutto (2013 IEEE International Conference on Advanced Networks and Telecommunications Systems (ANTS), 2013)
Multiple input multiple output (MIMO) technique that requires multiple antennas at both transmitter and the receiver is a key technology to meet the peak data rates and spectral efficiency targets of long term evolution (LTE) systems. MIMO is a widely researched topic, and understanding of MIMO concepts have an interaction with other essential enhancement mechanisms in the system including link adaptation, resource scheduling, inter stream interference, rank of the channel, etc. This paper mainly aims to target the MIMO mode adaptation strategies in LTE systems by considering the rank and other key parameters like antenna correlation, doppler frequency, bit rate, throughput, etc. 3GPP LTE rel-8 has adopted seven MIMO modes and variable modulation and coding schemes (MCS) to effectively utilize the available resources for maximizing the throughput of the system. In this paper, new techniques for obtaining appropriate rank and a new MIMO mode switching algorithm to maximize data rate of the user equipment (UE) for a given channel consider at the receiver with reasonable complexity, and there by improving the average system throughput are proposed. The paper considers only four MIMO modes namely transmit diversity, open loop spatial multiplexing (OLSM), closed loop spatial multiplexing (CLSM) and beam-forming with different modulation levels. MIMO mode switching is done based on throughput value between open loop modes namely transmit diversity and OLSM for high mobility UE in the presence of co channel interference (CCI). Similarly, mode switching is done between closed loop modes namely CLSM and beam-forming for pedestrian UE in the presence of CCI. Simulation results are provided to illustrate the performance benefits of the proposed algorithm. The simulation results reveal that these new techniques improves the system throughput significantly.